Discrimination Under Market Interdependence - Maroni, Yves R. (Quarterly Journal of Economics, 1947)
The problem: price policy in markets neither completely independent nor completely interrelated, 95. — I. Under monopolistic competition: price interdependence, 97; product interdependence, 98; “advertising” interdependence, 99; limited vs. unlimited discrimination, 100; freedom from price interdependence, 101; ability to enforce price differentials, 103. — II. A classification of cases: importance of substitutability, 106; coefficient expressing the relationship, 107; summary table, 109; relative size of markets, 112; comparison with interdependence between firms, 113. — III. Relation to the theory of international trade: four groups of cases, 113; complete independence, 115; interdependence, 116.